Implementasi Pendidikan Karakter Berbasis Agama di Madrasah Sebagai Bentuk Penanaman Karakter Pemimpin yang Ideal - Syukron Ma'mun (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2016)
This article discusses the character of an ideal leader. The ideal leader of a character is formed from two dimensional balanced angle that is common knowledge and religious knowledge. This is important in the context of a moral crisis that is currently afflicting our country. This paper was presented to discuss how the two dimensions that can be performed simultaneously. The object of the study, which provided the case study is a madrasa namely educational institutions of primary and secondary level. Remember education is not merely educate the child in intellect, but rather to build a whole personality and character, then with based on religion is absolute thing to do. The madrasa is one institution that combines religious education and public education so that the expected yield the ideal outcomes especially in forming the character of a leader.